Canadian poison control centres: preliminary assessment of their potential as a resource for public health surveillance. (November 2013) - Durigon, M.; Elliott, C.; Purssell, R.; Kosatsky, T.
Abstract Context. In the United States (US) and Europe, surveillance based on calls to poison control centres has identified new hazards and evolving exposure trends. In Canada, the value of poison control centre calls as a tool for health hazard surveillance is largely unrecognized. Objectives. This preliminary survey was undertaken to describe current operational characteristics and surveillance capacities at Canadian poison control centres and to determine potential for developing a Canadian poison control centre collaborative network. Methods. A structured quantitative–qualitative survey was administered to medical directors and clinical supervisors at the five Canadian poison control centres between March and May, 2012. Results. All five Canadian poison control centres operate 24/7 with each serving more than one province/territory. Annual call volumes range from 10, 000 to 58, 000. Data analysis is limited to detection of previously unrecognized hazards and short-term event-based adverse health monitoring. Currently no centre maintains systematic ongoing collection, integration and analysis of data. Constraints on personnel, resources and funding were identified as barriers to increasing capacity to provide and analyse call data. Conclusions. The potential exists to use Canadian poison control data as a novel source of public health surveillance. That they serve as sentinels for new or unexpected exposure events, have real-time electronic call-record capacity and demonstrate an interest in developing and sharing their call-record information supports their integration into existing public health networks.